Lexical transformations in the process of translation of English political terminology into Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The paper studies the types of lexical transformations of English political terminology in the process of its translation into Ukrainian. It deals with the aspects of translation techniques, with the pitfalls of  translator’s work.
Keywords: transformation; vocabulary correspondence; translation techniques; adequacy